Effective way to prevent visual disturbances due to Computer Vision Syndrome (CVS) - Chita Widia; Siti Zahara Rapida; Hanna Nurul Husna; Anih Kurnia; Eli Kurniasih (MEDIA ILMU KESEHATAN, 2023)
Background: Working too long with computers, including laptops, desktops, tablets and other display devices (such as smartphones and other electronic reading devices)for 3 hours continuously can increase the risk of eye health problems, one of these is Computer Vision Syndrome (CVS). One of the symptoms is visual symptoms, which consist of blurred vision and double vision Objective: This study intends to determine the effect of applying the 20-20-20 method on preventing visual symptoms of CVS. Methods: The research method used is a quantitative analytic method with a cross-sectional design. Results: The results of statistical analysis using the Wilcoxon test found that visual symptoms complaints after and before the application of 20-20-20 had an Asymp Sig value (2 tiles) 0f 0,005. The hypothesis in this study was accepted that there was a significant effect of the intervention 20-20-20 method because the value was 0.005 <0.05.Conclusion: The effective way to prevent visual symptoms of CVS is implementing 20-20-20 method.